Strengthening Pancasila Student Profile Based on Technological Pedagogical and Content Knowledge - Aeni, Kurotul; Andrijati, Noening; Astuti, Tri; Rosianingrum, Afifah; Afkawati, Salfaniar Hyda (JTP - Jurnal Teknologi Pendidikan, 2024)
Learning in elementary schools is currently directed to integrate technology that is aligned with the mission of the material in order to achieve quality results and student character, namely strengthening the profile of Pancasila students. This TPACK construction is expected to form student output as lifelong learners who have global abilities and behavior according to Pancasila values. Field studies need to analyze the integration of technology in learning as an effort to form students who are democratic, capable, and productive Indonesian citizens in the 21st century. The purpose of this study is to fundamentally analyze the model of strengthening the profile of Pancasila students based on TPACK at SDIT Usamah, Tegal City, as well as supporting factors and constraints. This type of research is descriptive qualitative; research location SDIT Usamah, Tegal City; data sources in the form of informants, activities, and documents; Data were collected using non-participant observation techniques, in-depth interviews, documentation studies; data validity testing by extending observations, increasing perseverance in research, discussions, triangulation. Data were analyzed using interactive model techniques flowing through data collection, data reduction, data display and conclusions. The results of the study indicate that strengthening the profile of Pancasila students based on TPACK at SDIT Usamah, Tegal City, especially in grade IV in science learning integrates technology applied through learning media and learning models. The dimensions of the Pancasila student profile are focused on three dimensions that are relevant to the material and objectives of science learning, including: 1) the dimension of global diversity; 2) the dimension of mutual cooperation; 3) the dimension of critical reasoning.